Multiple extradigital glomus tumors of the ankle and foot with limb hypoplasia in a child: a case report - Lim, Chiao Yee; Ng, Sijie; Duski, Suryasmi; Chye, Ping Ching (International Journal of Research in Orthopaedics, 2019)
Glomus tumors are rare tumors, and mostly occur in the fingertips and/ or subungual location. Multiple extradigital glomus tumors are extremely rare. We hereby described a rare case of multiple extradigital glomus tumor of the ankle and foot in a 11 year old girl with hypoplasia of the affected limb. The patient presented with swellings over her right ankle and foot for the past 5 years. The swellings were initially painless but became painful for the past 15 months. On examination, patient’s right leg and foot appeared to be smaller when compared to the left side. There were multiple vague swellings over the dorsum of right food and lateral aspect of right ankle, which were very tender to touch. There was no overlying skin changes observed. Magnetic resonance imaging showed multiple well defined, encapsulated lesions of varying sizes at the level of distal third right fibula and foot. The lesions appeared isointense to muscle in T1-weighted image, hyperintense in T2-weighted image with enhancement post-contrast. Excision biopsy of the right lateral distal leg swelling was performed. Histopathological examination of the excised mass confirmed the diagnosis of glomus tumor. In view of her parents were not keen for any further surgical intervention, the patient will be evaluated regularly, and any enlarging painful lesions will be excised as required. The clinical diagnosis of multiple extradigital glomus tumors is much more problematic due to its rarity. The physicians must be aware of this differential diagnosis so that early diagnosis and treatment could be administered to the patients.